ANALISIS PERTANGGUNG JAWABAN HUKUM ATAS KERUGIAN YANG DITIMBULKAN OLEH SISTEM KECERDASAN BUATAN MENURUT PERSPEKTIF HUKUM POSITIF - Saptaning Ruju Paminto; Azzahra Herawati; Dilla Ayu Pratiwi; Nispi Aliyatunnisa; Rizqi Ulmaliyah Alhaddi (Cahaya Ilmu Bangsa, 2024)
The development of information technology during this period tends to experience enormous changes and progress in society, and its development has both positive and negative impacts on human culture and civilization. Identification of the main problems examined in this research includes legal protection for victims of misuse of artificial intelligence and legal liability for losses caused by artificial intelligence. The method used is a normative juridical approach whose focus is to conduct research based on library references or secondary data carried out on norms and principles contained in secondary data sources, such as primary, secondary and tertiary legal materials. The results of this research state that legal protection for the use of electronic agents, such as AI, is strictly regulated in Indonesian legislation, especially in the ITE Law and PP 71 of 2019. Legal responsibility for losses caused by artificial intelligence also requires a legal entity. to know the consequences of committing or not committing an unlawful act. The implementation of AI deviations is in accordance with the relevant regulations, namely the ITE Law. The Civil Code recognizes legal responsibility for AI if it can fulfill the requirements of an unlawful act. An act that violates another person's rights or obligations is said to be an unlawful act.